2010
DOI: 10.1523/jneurosci.1737-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2G2019S Mutation Induces Dendrite Degeneration through Mislocalization and Phosphorylation of Tau by Recruiting Autoactivated GSK3β

Abstract: Intraneuronal tau aggregations are distinctive pathological features of Parkinson's disease (PD) with autosomal-dominant mutations in leucine-rich repeat kinase 2 (LRRK2). The most prevalent LRRK2 mutation, G2019S (glycine to serine substitution at amino acid 2019), causes neurite shrinkage through unclear pathogenetic mechanisms. We found that expression of G2019S mutant in Drosophila dendritic arborization neurons induces mislocalization of the axonal protein tau in dendrites and causes dendrite degeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
201
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(218 citation statements)
references
References 65 publications
16
201
1
Order By: Relevance
“…[53][54][55] Other studies have provided evidence supporting the direct activation of GSK-3β through physical interactions with mutant forms of LRRK-2, a gene commonly associated with increased risk of developing familial associated PD. 25,26 The aforementioned studies combined with our current results suggest that hyperactivation of GSK-3β may be the primary mechanism by which this protein is linked to PD (Figure 7). Indeed, a growing body of evidence from our laboratory and others define the important roles, kinases, such as GSK-3β, CK2, PLK2 and 3, and GRK1-5 have in the development and pathology of PD through the phosphorylation of α-Syn and Tau 16,[18][19][20][21][22][23][24][53][54][55][56][57] (Supplementary Table S3 and associated references).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…[53][54][55] Other studies have provided evidence supporting the direct activation of GSK-3β through physical interactions with mutant forms of LRRK-2, a gene commonly associated with increased risk of developing familial associated PD. 25,26 The aforementioned studies combined with our current results suggest that hyperactivation of GSK-3β may be the primary mechanism by which this protein is linked to PD (Figure 7). Indeed, a growing body of evidence from our laboratory and others define the important roles, kinases, such as GSK-3β, CK2, PLK2 and 3, and GRK1-5 have in the development and pathology of PD through the phosphorylation of α-Syn and Tau 16,[18][19][20][21][22][23][24][53][54][55][56][57] (Supplementary Table S3 and associated references).…”
Section: Discussionmentioning
confidence: 54%
“…Yet several studies have provided evidence that leucine-rich repeat kinase-2 (LRRK2), a kinase, that when mutated is involved in familial forms of PD, can directly interact with, and activate GSK-3β, resulting in increased p-TAU formation. 25,26 Among the kinases known to hyperphosphorylate Tau, glycogen synthase kinase-3β (GSK-3β) may be the most important given its ability to phosphorylate Tau at the majority of its serine/threonine sites that cause associated toxicities in AD. 27,28 The importance of GSK-3β is illustrated in that it is embryonically lethal when knocked out in mice.…”
mentioning
confidence: 99%
“…Furthermore, LRRK2 is expressed in NSCs isolated from both the DG and SVZ of E18.5 mice. The LRRK2 protein may interact with the regulator of neurite outgrowth during embryonic neurogenesis, CRMP2 [77] and numerous studies have demonstrated that mutant LRRK2 overexpression decreases neurite length/outgrowth, while LRRK2 deficits result in an increase of neurite length and arborization [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. Moreover, LRRK2 has been shown to bind Wnt signaling components (the DVL proteins) and play a role in the canonical Wnt/bcatenin signaling pathway, an important pathway for neurogenesis and in particular the development of DA neurons [83,95,96].…”
Section: Evidence For a Developmental Component Of Pd: Deregulated Emmentioning
confidence: 99%
“…Moreover, it has been demonstrated that pathogenic mutations of LRRK2 modulate its interaction with different Wnt pathway molecules, including DVL and GSK3, a component of the b-catenin destruction complex [83,95]. Importantly, KD of LRRK2 results in enhanced canonical Wnt signaling [96].…”
Section: Lrrk2 Is Involved In Wnt Signalingmentioning
confidence: 99%
“…Transgenic expression of human G2019S LRRK2 in Drosophila causes dendrite degeneration and dopaminergic (DA) neurons loss followed by locomotor dysfunction [114,115]. Importantly, this effect was diminished by pharmacological inhibition of kinase activity of G2019S mutant or by overexpression of parkin, a protein implicated in autosomalrecessive Parkinsonism [116,117].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%